Dietary fatty acids and risk of Alzheimer's disease and related dementias: Observations from the Washington Heights‐Hamilton Heights‐Inwood Columbia Aging Project (WHICAP). Issue 12 (27th July 2020) - Gustafson, Deborah R.; Bäckman, K.; Scarmeas, N.; Stern, Y.; Manly, J.J.; Mayeux, R.; Gu, Y.
Abstract: Introduction: High dietary intake of long chain, polyunsaturated fatty acids is associated with lower Alzheimer's disease (AD) risk. Methods: Washington Heights‐Hamilton Heights‐Inwood Columbia Aging Project is a multiethnic, prospective observational study of aging and dementia among elderly (≥ 65 years). Dietary intake was measured using a food frequency questionnaire. Dietary short‐, medium‐, and long‐chain fatty acid intakes were categorized by number of carbons and double bonds. Consensus AD diagnoses were made. Associations between AD risk and dietary fatty acid and cholesterol intakes were estimated using multivariable Cox proportional hazards regression models. Results: Of 2612 multiethnic women (67%) and men (baseline age 76.3 [6.4] years), 380 developed AD over an average 4.5 years follow‐up. Lower risk of AD was associated with increasing intakes of docosahexaenoic acid (DHA; hazard ratio [HR] = 0.73, 95% confidence interval [CI]: 0.57 to 0.95, P = 0.018) and eicosapentaenoic acid (EPA; HR = 0.74, 95% CI: 0.57 to 0.95, P = 0.021), and longer AD‐free survival ( P < 0.05). Discussion: Higher intake of DHA and EPA are protective for AD.